Mel Gibson. Remembered Reading: Memory, Comics and Post-War Constructions of British Girlhood. Leuven: Leuven UP, 2015. - Kristof Van Gansen (Studies in 20th & 21st Century Literature, 2017)
Review of Mel Gibson. Remembered Reading. Memory, Comics and Post-War Constructions of British Girlhood. Leuven: Leuven UP, 2015.
Keywords: Comics; children; gender; memory studies; history